2015
DOI: 10.1111/vru.12288
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and Magnetic Resonance Imaging Features of Inflammatory Versus Neoplastic Medial Retropharyngeal Lymph Node Mass Lesions in Dogs and Cats

Abstract: Medial retropharyngeal lymph node (MRLN) mass lesions are a common cause of cranial cervical masses in dogs and cats, and are predominantly due to metastatic neoplasia, primary neoplasia, or inflammatory lymphadenitis. The purpose of this retrospective cross-sectional study was to test the hypothesis that clinical and magnetic resonance imaging (MRI) characteristics for dogs and cats with MRLN mass lesions would differ for inflammatory vs. neoplastic etiologies. Dogs and cats with MRLN mass lesions that had un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, this feature may also be considered in a small number of cases as a normal node variant. Magnetic resonance imaging is another modality that can bring additional information in differentiating between neoplastic and inflammatory lymph nodes . Similar imaging features such as loss of the nodal hilus or heterogeneity are expected in metastatic lymph nodes due to tonsillar neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…However, this feature may also be considered in a small number of cases as a normal node variant. Magnetic resonance imaging is another modality that can bring additional information in differentiating between neoplastic and inflammatory lymph nodes . Similar imaging features such as loss of the nodal hilus or heterogeneity are expected in metastatic lymph nodes due to tonsillar neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of diffusion‐weighted MRI to differentiate between metastatic and benign lymph nodes has been demonstrated in human clinical studies as well as several experimental studies in animal models, where the ADC values of metastatic or malignant lymph nodes were found to be significantly lower than benign lymph nodes . The magnetic resonance appearance of presumed normal lymph nodes of the canine head and neck has been described, and a study evaluating the magnetic resonance appearance (not including diffusion‐weighted MRI) of neoplastic vs. inflammatory medial retropharyngeal lymph node mass lesions in both dogs and cats has been performed . However, to the authors’ knowledge, no studies have described the application of diffusion‐weighted MRI in the differentiation between benign and metastatic lymph nodes in dogs with naturally occurring disease.…”
Section: Introductionmentioning
confidence: 89%
“…Morphologic imaging techniques (such as computed tomography or magnetic resonance imaging (MRI)) can be used to detect enlarged lymph nodes, and previous veterinary studies have identified certain imaging characteristics that may aid in differentiation between benign (term used in this paper to include normal and reactive lymph nodes) and metastatic lymph nodes. Such imaging characteristics include perinodal contrast enhancement, presence of rim and/or heterogeneous contrast enhancement, and an abnormal hilus . These lymph node imaging characteristics may aid in ranking metastatic vs. benign diagnoses, although cytologic or histologic sampling is still required for confirmation.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study contradicts this statement, showing that this diagnostic tool demonstrates poor sensitivity in the detection of lymph node metastasis from tumours of canine head, particularly for micrometastasis (Skinner et al, 2018). Magnetic resonance imaging (MRI) may also be used for staging purposes, as it is superior in evaluation of soft tissue involvement compared to CT (Vestraete, 2005;Johnson et al, 2016).…”
Section: Clinical Stagingmentioning
confidence: 99%